Implementasi pemanfaatan lahan kosong untuk usaha ‎mikro kecil menengah: Perspektif siyasah dusturiyah sesuai Undang-Undang No ‎‎26 Tahun 2007 Pasal 33‎ - Rohinun, Fitria Nur Afifatur (Maliki Interdisciplinary Journal, 2023)
In writing this article, it discusses the use of vacant land for micro, small and medium enterprises in the perspective of siyasaha dustiriyah in accordance with Law No. 26 of 2007 article 33. Which basically land is one of the components of the earth's interior and has an important meaning for human life as a place or space of life with all its activities, as a source of life, even as a nation's government authority. So the purpose of this writing is to increase knowledge regarding how to use vacant land in accordance with law No. 26 of 2007. In this writing, it examines several points related to the use of vacant land, which are the principles that must be considered in order to be able to use land properly and according to the rule of law, as well as the use of vacant land according to siyasa dusturiyah which Islamic law applies to the State must work within the limits of their authority to build and carry out this social balance by using various methods and policies. Islamic law emphasizes a better standard of living with restrictions on excessive behavior and emphasizes that people who fall below the standard line increase their standard of living to meet the goals and objectives of societal balance.